2, 2′‐Bis(monoacylglycero) PO4 (BMP), but Not 3, 1′‐BMP, Increases Membrane Curvature Stress to Enhance α‐Tocopherol Transfer Protein Binding to Membranes. Issue 3 (21st January 2015) - Baptist, Matilda; Panagabko, Candace; Nickels, Jonathan D.; Katsaras, John; Atkinson, Jeffrey
Abstract: Previous work revealed that α‐tocopherol transfer protein (α‐TTP) co‐localizes with bis(monoacylglycero)phosphate (BMP) in late endosomes. BMP is a lipid unique to late endosomes and is believed to induce membrane curvature and support the multivesicular nature of this organelle. We examined the effect of BMP on α‐TTP binding to membranes using dual polarization interferometry and vesicle‐binding assay. α‐TTP binding to membranes is increased by the curvature‐inducing lipid BMP. α‐TTP binds to membranes with greater affinity when they contain the 2, 2′‐BMP versus 3, 1′‐BMP isomers.